Post-immersive Listening: Perspectives on the Mediation of Sonic Environments - Budhaditya Chattopadhyay (Revista Vortex)
Unplanned meetings can stem from complex movements across geographies, with serendipity playing a key role. Media artist Budhaditya Chattopadhyay unexpectedly meets researcher Budhaditya Chattopadhyay at a café in Budapest. This is their eighth meeting, following previous encounters in Copenhagen (2017), Den Haag (2021c), Kolkata (2021b), Berlin (2022a), Beirut (2022b), Basel (2023), and Rampurhat (2024). Each interaction has fostered a reflexive exchange of ideas, merging their artistic and theoretical perspectives on sound, listening, migratory experiences, and decolonial activism. Despite the differing lenses they bring, their conversations generate new insights. In the bustling café, surrounded by disengaged students emblematic of the isolation in European universities, the two engage in thoughtful discussions on acoustic ecologies, sonic environments, field recording, and audiovisual media. Their dialogue embodies a spirit of camaraderie, underscoring the value of interdisciplinary exchanges in nurturing knowledge and understanding across artistic and scholarly domains.